2020
DOI: 10.1177/1461444820902103
|View full text |Cite
|
Sign up to set email alerts
|

Understanding third-person perception about Internet privacy risks

Abstract: This study aims to test the third-person effect (TPE) in the perception of Internet privacy risks. Support was found for a TPE model suggesting that users report greater perceived Internet privacy risks on others than on themselves, based on a sample ( N = 613) from Amazon MTurk. In particular, the differential perception of Internet privacy risks between self and others increased people’s willingness to recommend protective measures to others but decreased their willingness to adopt protective measures themse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Perceived negative influence on self/others: Based on several previous studies where researchers gaged presumed media influence on self or others using one item (e.g. Chen and Atkin, 2021;Ho et al, 2019), the present study adapted one item from Schweisberger et al (2014) to measure perceived negative influence on self. We used a seven-point Likert scale (1 5 strongly disagree and 7 5 strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Perceived negative influence on self/others: Based on several previous studies where researchers gaged presumed media influence on self or others using one item (e.g. Chen and Atkin, 2021;Ho et al, 2019), the present study adapted one item from Schweisberger et al (2014) to measure perceived negative influence on self. We used a seven-point Likert scale (1 5 strongly disagree and 7 5 strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…However, privacy concerns are not a new phenomenon; these incidents repeatedly evolve when an individual perceives a threat from an innovative information technology (I.T.) that develops the surveillance, storage, retrieval, and communication of personal information [27,28].…”
Section: Privacy Concern and Educational Technologymentioning
confidence: 99%
“…With the rapid advancement of educational technologies, the exchange of students' information has become more convenient [25]. E-learning service providers have better and more sophisticated ways to access and collect personal information; therefore, gaining a student's personal information has become more accessible [27]. As a result, privacy concerns about personal information accelerate tremendously among students as a considerable amount of personal information is interchanged, stored, and shared [28].…”
Section: Privacy Concern and Educational Technologymentioning
confidence: 99%
“…Prior studies investigating the TPP in terms of risk perception have confirmed the pattern that people significantly perceive less risk to themselves than others. For instance, Chen and Atkin investigated TPE in the context of Internet privacy risks and found that users reported greater risk perception to others than to themselves [ 52 ]. This biased optimism was also discovered when facing health risks such as cancer [ 53 ] and avian flu [ 54 ].…”
Section: Literature Reviewmentioning
confidence: 99%